Serum calcium levels and neuropsychological performance in depression and matched healthy controls: Reversal of correlation a marker of the aging cognitive clock? - Grützner, Thea M.; Flach, Daniel; Weisbrod, Matthias; Roesch-Ely, Daniela; Sharma, Anuradha (Psychoneuroendocrinology, 2018)
Background - Major depressive disorder (MDD) is associated with cognitive impairment, that might be related to disturbed calcium homeostasis. Calcium-related processes have also been implicated in age related cognitive decline. Since serum calcium and brain interstitial fluids maintain long-term equilibrium under normal physiological states, serum calcium levels could affect neuronal and hence cognitive function. High serum calcium has been associated with cognitive decline in geriatric populations, whereas evidence for MDD and healthy populations is less consistent. - Methods - Differences in neuropsychological (NPS) performance and their relationship with serum calcium (total, ionized, total to ionized ratio) in (partially) remitted MDD patients (n=59) and healthy controls (HC) (n=59) individually matched for age, gender and education (age-range 19-60years) were examined. Modulation of study parameters and their interaction by the factor age was investigated, with subgroups young and old divided at median=37years. Participants provided blood samples and completed an extensive NPS test battery. - Results - MDD showed significantly poorer NPS performance compared to HC. Serum calcium associated positively with NPS performance in HC and negatively in MDD for entire age-range samples. While younger MDD and HC showed positive NPS-calcium correlations, older MDD and HC exhibited negative NPS-calcium correlations (‘correlation reversal'). Age had a significant effect on cognition and ionized calcium and interacted with illness-status, with an exaggerated influence on cognition in MDD compared to HC. - Conclusions - The results place calcium ‘correlation reversal’ to early middle-age time window, which may be accelerated for MDD and highlight the central role of calcium pathways in normal and pathological cognitive aging.
Gesehen am 20.05.2019